Performance Audit of National AIDS Control Programme in Punjab - CAG of India (CAG of India, 2002)
Acquired Immuno Deficiency Syndrome (AIDS) is a fatal disease caused by a virus called the Human Immuno Deficiency Virus (HIV). It has emerged as a serious public health problem. National AIDS Control Programme (NACP) was initiated in the country in 1985 in collaboration with Indian Council of Medical Research. Subsequently, in order to contain the spread of HIV/AIDS, Government of India (GOI) launched (1992) a hundred per cent Centrally sponsored programme (Programme) with World Bank assistance. The GOI established National AIDS Control Organization (NACO) an executive body in the Ministry of Health and Family Welfare headed by Additional Secretary as Project Director. The project was implemented in two phases. The objectives of the National AIDS Control Programme Phase-I (NACP-I) were (i) to slow the spread of HIV; (ii) to decrease morbidity and mortality associated with HIV; (iii) to minimize socio economic impact resulting for HIV infection. The National AIDS Control Programme Phase-II (NACP-II) was launched in November 1999 with two key objectives namely to (1) reduce spread of HIV infection in India and (2) strengthen India’s capacity to respond to HIV/AIDS on long term basis. The implementation of the National AIDS Control Programme in Punjab for the period 1996-2001 was reviewed in audit during December 2000 to April 2001 by checking the records of AIDS Control Cell in the office of DHS, Punjab State AIDS Control Society and Civil Surgeons of 10 districts. The performance audit revealed that the programme was not effectively managed and implemented. The achievements under sub-components were not substantial and in most of the cases targets were not fixed. The activities particularly under priority targeted intervention for groups at high risk and low cost AIDS care components were negligible and whatever the achievements were there under other components remained dormant due to lack of effective management, implementation and monitoring and evaluation of the programme at State level. The counsellors were neither appointed by the Society due to less salary nor any steps were taken with the NACO to increase the salary of the counsellors which deprived the benefits of counseling to the intended beneficiaries. The Society had sufficient balance in its account as on March, 2001 due to less expenditure on all the components. No expenditure was incurred for training of NGOs. The condom vending machines purchased for awareness of AIDS programme were defective which defeated the purpose for which these were purchased.
For the Period 1996-97 to 2000-01